Prevalence and risk factors of gestational diabetes mellitus among pregnant women in northern Vietnam: a cross-sectional study - Hieu Minh Le; Thi Ai Nguyen; Dang Kien Nguyen; Ditte Søndergaard Linde; Ib Christian Bygbjerg; Jens Søndergaard; Thanh Duc Nguyen; Bay Quang Nguyen; Ngoc-Anh Thi Dang; Xuan Bai Nguyen; Dan W. Meyrowitsch; Christina A. Vinter; et al. (Global Health Action)
Background Gestational diabetes mellitus (GDM) increases adverse neonatal and maternal outcomes. Understanding the prevalence and risk factors of GDM is necessary to plan health care interventions and policy. Objective To determine the prevalence and risk factors of GDM in Thai Binh, Vietnam. Methods A cross-sectional study was conducted in two health facilities in Thai Binh, Vietnam, with the participation of 1,106 pregnant women. Women were recruited at their first antenatal care visit where face-to-face interviews about socioeconomic and reproductive factors were performed. A 2-hour 75 g oral glucose tolerance test was conducted at 24–28 weeks of gestation. GDM was diagnosed according to the World Health Organization 2013 criteria. Logistic regression analyses were used to assess the factors associated with GDM. Results The prevalence rate of GDM was 27.1%. Multivariate logistic regression analysis showed maternal age from 25 to 34 (adjusted OR 2.0; 95%CI 1.3–2.9), maternal age ≥ 35 (adjusted OR 3.0; 95%CI 1.7–5.4), pregestational body mass index ≥ 23 (adjusted OR 1.6; 95%CI 1.1–2.3), family history of diabetes (adjusted OR 1.9; 95%CI 1.3–2.9), fertility treatment (adjusted OR 2.3; 95%CI 1.3–3.8), and previous GDM (adjusted OR 3.1; 95%CI 1.4–6.9) were associated with increased odds of GDM. Conclusions More than one-fourth of pregnant women in Thai Binh, Vietnam, may have GDM. Advanced maternal age, high pregestational body mass index, family history of diabetes, and previous GDM were associated with increased risk of GDM. Additionally, fertility treatment appears to be strongly associated with an increased risk of GDM.